2018
DOI: 10.1371/journal.pone.0191838
|View full text |Cite
|
Sign up to set email alerts
|

CLC-Pred: A freely available web-service for in silico prediction of human cell line cytotoxicity for drug-like compounds

Abstract: In silico methods of phenotypic screening are necessary to reduce the time and cost of the experimental in vivo screening of anticancer agents through dozens of millions of natural and synthetic chemical compounds. We used the previously developed PASS (Prediction of Activity Spectra for Substances) algorithm to create and validate the classification SAR models for predicting the cytotoxicity of chemicals against different types of human cell lines using ChEMBL experimental data. A training set from 59,882 str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(103 citation statements)
references
References 45 publications
(41 reference statements)
1
100
0
2
Order By: Relevance
“…For each molecule, the Pa (probable activity) and Pi (probable inactivity) values, both ranging from 0,000 to 1,000, were reported. Higher values of Pa are associated with a higher probability to obtain that effect experimentally, although some real activities could be lost ( 44 ). The study reported only the cytostatic, cytotoxic and antimicrobial activities of the selected compounds, with a Pa>0,700.…”
Section: Methodsmentioning
confidence: 99%
“…For each molecule, the Pa (probable activity) and Pi (probable inactivity) values, both ranging from 0,000 to 1,000, were reported. Higher values of Pa are associated with a higher probability to obtain that effect experimentally, although some real activities could be lost ( 44 ). The study reported only the cytostatic, cytotoxic and antimicrobial activities of the selected compounds, with a Pa>0,700.…”
Section: Methodsmentioning
confidence: 99%
“…In silico cytotoxicity screening was performed by cell line cytotoxicity predictor (CLC-Pred) as per published protocol ( Lagunin et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…In-silico cytotoxicity screening was performed using online CLC-Pred (Cell line Cytotoxicity Predictor) as per published protocol ( Lagunin et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%